PERANAN KEPALA DESA DALAM MENINGKATKAN KINERJA APARATUR PERANGKAT DESA DI DESA CEMBA KECAMATAN ENREKANG KABUPATEN ENREKANG - Razman Razak; Baharuddin Baharuddin; Elihami Elihami; Harmayanti Harmayanti (Universitas Muhammadiyah Enrekang, 2021)
Village heads in carrying out their daily duties, especially those related to the presentation of the data and information needed, are increasingly required to have hard work and optimal abilities to facilitate the implementation of government duties. This study aims to determine how the role of the village head in improving the performance of the village apparatus in Cemba Village, Enrekang Regency. The type of research that the author uses is field research (field research) which is descriptive. In collecting data using data collection methods using observation, interviews and documentation. Based on the results of this study, it was concluded that there were efforts to increase the ability of the Cemba Village apparatus in carrying out government administrative tasks, especially village government administration which included: Employee discipline development, education and training, work motivation, and career development.